1999
DOI: 10.2494/photopolymer.12.27
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Surface Functionalization under Cold-plasma Conditions.

Abstract: Controlled, plasma-mediated, surface modification of various substrates including inorganic and organic polymers is essential for the creation of miniaturized advanced materials. Many of these approaches have focused on the surfaceimplantation of specific chemical groups which can be employed for subsequent chemical reactions where molecular recognition plays a significant role (e,g, immobilization of biomolecules; preparation of catalysts, etc.). The deposition of predesigned-structure thin macromolecular lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…Surface functionalization by air plasma could change the physical and chemical properties of the seed coat, thereby interrupting their dormancy and initiating germination 7 . The plasma environment is conducive to generation of bioactive small molecules that can interact with and deposit onto the seed envelope 42 and penetrate into the seed to a depth of up to 10 nm 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Surface functionalization by air plasma could change the physical and chemical properties of the seed coat, thereby interrupting their dormancy and initiating germination 7 . The plasma environment is conducive to generation of bioactive small molecules that can interact with and deposit onto the seed envelope 42 and penetrate into the seed to a depth of up to 10 nm 43 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the fluorine:carbon (F:C) ratios of specific fluorocarbon derivatives (rather than the experimental parameters) control the macromolecular‐structure forming processes; high values of this parameter shift the mechanisms towards ablation (etching) reactions, while low values of these ratios lead to fluorocarbon‐layer depositions. Numerous reaction mechanisms have been suggested for the formation of fluorocarbon‐type structures (Denes et al, 1997, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…In other instances, delayed germination To increase seedling growth directly, a seed treatment has been investigated through retardation of imbibition may involve direct application of nutrients or plant to prevent inhibitional chilling damage of seed sown in a cold, wet soil (Priestly and Leopold, 1986;Taylor et chie, 1978;Glick, 1995;Bashan, 1998). To enhance nutri-places macromolecular plasma chemistry in the sphere of advanced technology (Denes et al, 1999; Denes, ent uptake, some investigators have treated seeds with beneficial microorganisms that can proliferate on the 1997). The most commonly used plasma reactors for the seed and improve nitrogen fixation (Tonkin, 1984;Kanvinde and Sastry, 1990).…”
mentioning
confidence: 99%
“…Cold plasma treatment has been a fast, economical, and green method to enhance seed performance [Denes et al, 1999;Yin et al, 2005;Dhayal et al, 2006;Sera et al, 2010;Li et al, 2014]. Previous studies demonstrated that cold plasma treatment could improve seed germination and fast growth of several plants such as Carthamus tinctorium L [Dhayal et al, 2006], wheat [Sera et al, 2010], tomato [Yin et al, 2005], soybean , poppy seed [Sera et al, 2013], and cannabis [Sera et al, 2016], and it could significantly increase crop yields [Yin et al, 2005].…”
Section: Introductionmentioning
confidence: 99%